2004
DOI: 10.1177/0091270004268050
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a Clinically Relevant Interaction Between Etanercept and Digoxin

Abstract: Etanercept, a soluble recombinant human tumor necrosis factor receptor (TNFr), is effective and well tolerated in the treatment of rheumatoid arthritis, juvenile rheumatoid arthritis, psoriatic arthritis, ankylosing spondylitis, and psoriasis. The primary objective of this study was to investigate the potential pharmacokinetic and pharmacodynamic interaction between digoxin and etanercept at steady state. In a crossover, open-label, nonrandomized, 3-period study, 12 healthy male subjects received loading oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Many pharmacokinetic studies of etanercept conducted in healthy subjects have shown that these biologic agents are well tolerated. [11,[18][19][20][21] In addition, a previous population-based pharmacokinetic study of etanercept indicated that the pharmacokinetics in rheumatoid arthritis and ankylosing spondylitis patients is similar to that in healthy volunteers. [22][23][24] Therefore, reconstituted lyophilized (25 mg mL) HD203 and Enbrel Ò can be expected to result in similar pharmacokinetics in the clinical setting.…”
Section: Discussionmentioning
confidence: 96%
“…Many pharmacokinetic studies of etanercept conducted in healthy subjects have shown that these biologic agents are well tolerated. [11,[18][19][20][21] In addition, a previous population-based pharmacokinetic study of etanercept indicated that the pharmacokinetics in rheumatoid arthritis and ankylosing spondylitis patients is similar to that in healthy volunteers. [22][23][24] Therefore, reconstituted lyophilized (25 mg mL) HD203 and Enbrel Ò can be expected to result in similar pharmacokinetics in the clinical setting.…”
Section: Discussionmentioning
confidence: 96%
“…Almost all digoxin interaction studies have been carried out at the maintenance dose of 0.25 mg. The mean C max in these studies ranged from 1.16 to 3.70 ng/mL (Table 1) [4][5][6][7][8][9][10]. Depending on the situation, side effects may be caused by exceeding the upper limit of recommended therapeutic plasma concentration.…”
Section: Introductionmentioning
confidence: 97%
“…When combined with anakinra, an increased incidence of infections was observed. Etanercept did not show interactions with warfarin [87], methotrexate [88] and digoxin [89].…”
Section: Medication Interactionsmentioning
confidence: 84%